Method for producing sulfide-based inorganic solid electrolyte material

CN116812887BActive Publication Date: 2026-10-30FURUKAWA COMPANY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310824108.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-06
Publication Date
2026-10-30
Estimated Expiration
2040-03-06

AI Technical Summary

Benefits of technology

[0017]根据本发明,能够提供能够在更短的时间内进行玻璃化工序且能够缩短制造时间的硫化物系无机固体电解质材料的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004324452530000131
    Figure BDA0004324452530000131
Patent Text Reader

Abstract

Provided is a method for producing a sulfide inorganic solid electrolyte material, which is a method for producing a sulfide inorganic solid electrolyte material containing Li, P, and S as constituent elements, the method comprising: a preparation step of preparing a raw inorganic composition (A) containing at least lithium sulfide, phosphorus sulfide, and a crystallization nucleating agent; and a glassification step of glassifying the raw inorganic composition (A) by mechanically processing the raw inorganic composition (A).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the application filed on March 6, 2020, with application number 202080023463.3 and invention title "Method for manufacturing sulfide-based inorganic solid electrolyte materials". Technical Field

[0002] This invention relates to a method for manufacturing sulfide-based inorganic solid electrolyte materials. Background Technology

[0003] Lithium-ion batteries are commonly used as power sources for small portable devices such as mobile phones and laptops. In addition, recently, lithium-ion batteries have also begun to be used as power sources for electric vehicles and energy storage, in addition to small portable devices.

[0004] Currently available lithium-ion batteries use electrolytes containing flammable organic solvents. On the other hand, lithium-ion batteries that use a solid electrolyte, thus making the battery entirely solid-state (hereinafter also called all-solid-state lithium-ion batteries), do not use flammable organic solvents within the battery. Therefore, they are considered to offer simplification of safety devices and superior manufacturing costs and productivity. For example, sulfide-based solid electrolyte materials are known as solid electrolyte materials used in such batteries.

[0005] For example, Patent Document 1 (Japanese Patent Application Publication No. 2016-27545) describes a sulfide-based solid electrolyte material, characterized by a peak at a position of 2θ = 29.86° ± 1.00° in X-ray diffraction measurements using CuKα rays, exhibiting Li 2y+3 The composition of PS4 (0.1≤y≤0.175).

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent document 1: Japanese Patent Application Publication No. 2016-27545. Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] The sulfide-based inorganic solid electrolyte material described in Patent Document 1 is generally obtained by vitrification of a raw material inorganic composition containing two or more inorganic compounds that are raw materials for the inorganic solid electrolyte material through mechanical processing by methods such as mechanical grinding.

[0011] However, according to the research of the inventors, the process of vitrifying the raw inorganic composition by mechanical treatment is very time-consuming and has poor productivity. In other words, the method for manufacturing sulfide-based inorganic solid electrolyte materials, including the aforementioned process of vitrifying the raw inorganic composition by mechanical treatment, is not suitable for industrial production.

[0012] The present invention was made in view of the above circumstances, and provides a method for manufacturing a sulfide-based inorganic solid electrolyte material that can perform the vitrification process in a shorter time and can shorten the manufacturing time.

[0013] Methods for solving problems

[0014] The inventors have conducted repeated and dedicated research to achieve the aforementioned objectives. They discovered that by including a nucleating agent in the inorganic composition of the raw materials before the vitrification process, the vitrification process of the inorganic composition can be shortened, thus completing this invention.

[0015] According to the present invention, a method for manufacturing a sulfide-based inorganic solid electrolyte material is provided. This method is for manufacturing a sulfide-based inorganic solid electrolyte material containing Li, P, and S as constituent elements. The method includes: a preparation step, which prepares a raw material inorganic composition (A) containing at least lithium sulfide, phosphorus sulfide, and a nucleating agent; and a vitrification step, which vitrifies the raw material inorganic composition (A) by mechanically treating it.

[0016] The effects of the invention

[0017] According to the present invention, a method for manufacturing sulfide-based inorganic solid electrolyte materials is provided, which enables the vitrification process to be performed in a shorter time and shortens the manufacturing time. Detailed Implementation

[0018] The embodiments of the present invention will now be described. It should be noted that, unless otherwise specified, the numerical range "A~B" means above A and below B.

[0019] First, the method for manufacturing the sulfide-based inorganic solid electrolyte material of this embodiment will be explained.

[0020] The method for manufacturing a sulfide-based inorganic solid electrolyte material according to this embodiment is a method for manufacturing a sulfide-based inorganic solid electrolyte material containing Li, P and S as constituent elements. It includes: a preparation step, in which a raw material inorganic composition (A) containing at least lithium sulfide, phosphorus sulfide and a crystal nucleating agent is prepared; and a vitrification step, in which the raw material inorganic composition (A) is vitrified by mechanically treating the raw material inorganic composition (A).

[0021] According to the manufacturing method of the sulfide-based inorganic solid electrolyte material of this embodiment, compared with the conventional manufacturing method, the vitrification process of the inorganic composition can be shortened, and as a result, the manufacturing time of the sulfide-based inorganic solid electrolyte material of this embodiment can be shortened.

[0022] The sulfide-based inorganic solid electrolyte material obtained by the manufacturing method of the sulfide-based inorganic solid electrolyte material of this embodiment contains Li, P and S as constituent elements.

[0023] Furthermore, regarding the sulfide-based inorganic solid electrolyte material of this embodiment, from the viewpoint of further improving lithium-ion conductivity, electrochemical stability, stability in moisture or air, and operability, the molar ratio of the Li content to the P content in the sulfide-based inorganic solid electrolyte material, Li / P, is preferably 1.0 or more and 10.0 or less, more preferably 1.0 or more and 5.0 or less, even more preferably 2.0 or more and 4.5 or less, even more preferably 3.0 or more and 4.2 or less, even more preferably 3.3 or more and 4.0 or less, and particularly preferably 3.3 or more and 3.8 or less.

[0024] Furthermore, the molar ratio of the content of S to the content of P is preferably 1.0 or more and 10.0 or less, more preferably 2.0 or more and 6.0 or less, even more preferably 3.0 or more and 5.0 or less, even more preferably 3.5 or more and 4.5 or less, and particularly preferably 3.8 or more and 4.2 or less.

[0025] Here, the contents of Li, P and S in the sulfide-based inorganic solid electrolyte material of this embodiment can be determined, for example, by ICP-luminescence spectrophotometry or X-ray analysis.

[0026] The sulfide-based inorganic solid electrolyte material of this embodiment can be used for any application requiring lithium-ion conductivity. Preferably, the sulfide-based inorganic solid electrolyte material of this embodiment is used in lithium-ion batteries. More specifically, it is used in the positive electrode active material layer, negative electrode active material layer, and electrolyte layer in lithium-ion batteries. Furthermore, the sulfide-based inorganic solid electrolyte material of this embodiment is suitable for constituting the positive electrode active material layer, negative electrode active material layer, and solid electrolyte layer of an all-solid-state lithium-ion battery, and is particularly suitable for constituting the solid electrolyte layer of an all-solid-state lithium-ion battery.

[0027] As an example of an all-solid-state lithium-ion battery using a sulfide-based inorganic solid electrolyte material according to this embodiment, a battery in which the positive electrode, solid electrolyte layer, and negative electrode are stacked in this order can be cited.

[0028] The following is a detailed explanation of each process.

[0029] (Preparation process)

[0030] First, a raw material inorganic composition (A) containing at least lithium sulfide, phosphorus sulfide, and a nucleating agent is prepared. The raw material inorganic composition (A) can be obtained, for example, by mixing the raw materials in a specified molar ratio to achieve the desired composition ratio of the target sulfide-based inorganic solid electrolyte material.

[0031] Here, the mixing ratio of each raw material in the raw material inorganic composition (A) is adjusted so that the obtained sulfide-based inorganic solid electrolyte material reaches the desired composition ratio.

[0032] As for the method of mixing the raw materials, there are no particular limitations as long as the mixing method can mix the raw materials evenly. For example, ball mills, bead mills, vibratory mills, impact crushing devices, mixers (pug mixers, screw mixers, drum mixers, cylindrical mixers, V-type mixers, etc.), kneaders, twin-shaft kneaders, air jet mills, etc. can be used for mixing.

[0033] The mixing conditions, such as stirring speed, processing time, temperature, reaction pressure, and gravitational acceleration applied to the mixture, can be appropriately determined according to the processing volume of the mixture.

[0034] There are no particular limitations on the lithium sulfide used as a raw material; commercially available lithium sulfide or lithium sulfide obtained, for example, by reacting lithium hydroxide with hydrogen sulfide, can be used. From the viewpoint of obtaining high-purity sulfide-based inorganic solid electrolyte materials and suppressing side reactions, lithium sulfide with fewer impurities is preferred.

[0035] In this embodiment, lithium polysulfides are also included in the lithium sulfide. Li₂S is preferred as the lithium sulfide.

[0036] There are no particular limitations on the phosphorus sulfide used as a raw material, and commercially available phosphorus sulfides (e.g., P2S5, P4S3, P4S7, P4S5, etc.) can be used. From the viewpoint of obtaining high-purity sulfide-based inorganic solid electrolyte materials and suppressing side reactions, phosphorus sulfide with fewer impurities is preferred. As phosphorus sulfide, P2S5 is preferred.

[0037] Inorganic solid electrolyte materials can be used as nucleating agents for crystallization, for example, as raw materials.

[0038] There are no particular limitations on the aforementioned inorganic solid electrolyte materials, and examples include sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials. Among these, from the viewpoint of further improving the ionic conductivity of the obtained sulfide-based inorganic solid electrolyte material, sulfide-based inorganic solid electrolyte materials are preferred as crystal nucleating agents used as raw materials, and sulfide-based inorganic solid electrolyte materials containing Li, P, and S as constituent elements are more preferred.

[0039] Furthermore, there are no particular limitations on the aforementioned inorganic solid electrolyte material; for example, materials used to form the solid electrolyte layer of an all-solid-state lithium-ion battery can be cited.

[0040] Examples of sulfide-based inorganic solid electrolyte materials include, for instance, Li₂S-P₂S₅, Li₂S-SiS₂, Li₂S-GeS₂, Li₂S-Al₂S₃, Li₂S-SiS₂-Li₃PO₄, Li₂S-P₂S₅-GeS₂, Li₂S-Li₂O-P₂S₅-SiS₂, Li₂S-GeS₂-P₂S₅-SiS₂, Li₂S-SnS₂-P₂S₅-SiS₂, Li₂S-P₂S₅-Li₃N, and Li₂S₂S₂S₅. 2+X -P4S3 materials, Li2S-P2S5-P4S3 materials, etc.

[0041] From the viewpoint of excellent lithium-ion conductivity and stability without decomposition over a wide voltage range, Li2S-P2S5 materials are preferred. Here, for example, Li2S-P2S5 materials refer to inorganic materials obtained by mechanically reacting an inorganic composition containing at least Li2S (lithium sulfide) and P2S5 (phosphorus sulfide) with each other.

[0042] In this embodiment, lithium polysulfides are also included in the lithium sulfide.

[0043] Examples of oxide-based inorganic solid electrolyte materials include, for example, NASICON-type materials such as LiTi2(PO4)3, LiZr2(PO4)3, and LiGe2(PO4)3, and (La... 0.5+x Li 0.5-3x Perovskite materials such as TiO3, Li2O-P2O5 materials, and Li2O-P2O5-Li3N materials.

[0044] Other lithium-based inorganic solid electrolyte materials include, for example, LiPON, LiNbO3, LiTaO3, Li3PO4, and LiPO4. 4-x N x(x is 0 < x ≤ 1), LiN, LiI, LISICON, etc.

[0045] Furthermore, the glass-ceramics obtained by crystallizing these inorganic solid electrolytes can also be used as inorganic solid electrolyte materials.

[0046] Sulfide-based inorganic solid electrolyte materials used as nucleating agents for crystallization are preferably materials that have lithium-ion conductivity and contain Li, P, and S as constituent elements.

[0047] Furthermore, for sulfide-based inorganic solid electrolyte materials used as nucleating agents, from the viewpoint of further improving the lithium-ion conductivity, electrochemical stability, stability in moisture or air, and operability of the obtained sulfide-based inorganic solid electrolyte materials, the molar ratio of the content of Li to the content of P in the sulfide-based inorganic solid electrolyte material, Li / P, is preferably 1.0 or more and 10.0 or less, more preferably 1.0 or more and 5.0 or less, further preferably 2.0 or more and 4.5 or less, even more preferably 3.0 or more and 4.2 or less, even more preferably 3.3 or more and 4.0 or less, and particularly preferably 3.3 or more and 3.8 or less.

[0048] Furthermore, the molar ratio of the content of S to the content of P is preferably 1.0 or more and 10.0 or less, more preferably 2.0 or more and 6.0 or less, even more preferably 3.0 or more and 5.0 or less, even more preferably 3.5 or more and 4.5 or less, and particularly preferably 3.8 or more and 4.2 or less.

[0049] Here, the contents of Li, P and S in the sulfide-based inorganic solid electrolyte material used as a nucleating agent can be determined, for example, by ICP-luminescence spectrophotometry or X-ray photoelectron spectrophotometry.

[0050] The shape of inorganic solid electrolyte materials used as nucleating agents for crystallization can be, for example, particulate. There are no particular limitations on particulate inorganic solid electrolyte materials; the average particle size d is determined by the weight-based particle size distribution measured using laser diffraction scattering particle size distribution method. 50 Preferably, the micrometer is 1 μm or more and 50 μm or less, more preferably 2 μm or more and 40 μm or less, and even more preferably 3 μm or more and 35 μm or less.

[0051] Regarding the content of the nucleating agent contained in the raw material inorganic composition (A), from the viewpoint of further shortening the vitrification process, when the total content of the raw material inorganic composition (A) is set to 100% by mass, it is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more. Regarding the upper limit of the content of the nucleating agent contained in the raw material inorganic composition (A), from the viewpoint of reducing the amount of nucleating agent used and increasing the production quantity of the obtained sulfide-based inorganic solid electrolyte material, it is preferably 60% by mass or less, more preferably 50% by mass or less, further preferably 45% by mass or less, and particularly preferably 35% by mass or less.

[0052] Lithium nitride can also be used as a raw material. Here, the nitrogen in lithium nitride is discharged into the system in the form of N2. Therefore, by using lithium nitride as an inorganic compound raw material, the Li composition can be increased only compared to sulfide-based inorganic solid electrolyte materials that contain Li, P, and S as constituent elements.

[0053] The lithium nitride used in this embodiment is not particularly limited; commercially available lithium nitride (e.g., Li3N) or lithium nitride obtained by reacting metallic lithium (e.g., Li foil) with nitrogen gas can be used. From the viewpoint of obtaining a high-purity solid electrolyte material and suppressing side reactions, lithium nitride with fewer impurities is preferred.

[0054] (Vitrification process)

[0055] Then, the raw material inorganic composition (A) is vitrified by mechanical treatment. That is, lithium sulfide and phosphorus sulfide, which are raw materials, are chemically reacted and vitrified to obtain a sulfide-based inorganic solid electrolyte material in a glassy state.

[0056] Here, mechanical treatment refers to a process that causes two or more inorganic compounds to undergo a chemical reaction and vitrification by mechanically impacting them; examples include mechanochemical treatment.

[0057] Furthermore, in the vitrification process, from the viewpoint of easily achieving an environment with a high level of removal of moisture and oxygen, it is preferable to carry out mechanical processing in a dry manner, and more preferably, dry mechanical-chemical processing.

[0058] If mechanochemical processing is used, the contact area between the raw materials can be increased because they can be mixed while being pulverized into microparticles. This promotes the reaction of the raw materials, thus enabling the sulfide-based inorganic solid electrolyte material of this embodiment to be obtained more efficiently.

[0059] Here, mechanochemical treatment refers to a method of vitrification that simultaneously applies mechanical energy such as shear force, impact force, or centrifugal force to the composition as the object. Examples of apparatus for vitrification via mechanochemical treatment include pulverizers / dispersers such as ball mills, bead mills, vibratory mills, turbo mills, mechanical fusion machines, disc mills, and roller mills; rotary / impact pulverizing devices, such as rock drills, vibratory drills, and impact actuators, which combine rotation (shear stress) and impact (compressive stress); and high-pressure grinding rollers. Among these, ball mills and bead mills are preferred from the viewpoint of efficiently generating very high impact energy, with ball mills being particularly preferred. Furthermore, from the viewpoint of excellent continuous production, roller mills, rotary / impact pulverizing devices, such as rock drills, vibratory drills, and impact actuators, which combine rotation (shear stress) and impact (compressive stress), and high-pressure grinding rollers are preferred.

[0060] Furthermore, it is preferable to carry out the mechanochemical treatment in an inactive environment. This suppresses the reaction between sulfide-based inorganic solid electrolyte materials and water vapor, oxygen, etc.

[0061] Furthermore, the aforementioned inactive environment refers to a vacuum environment or an inactive gas environment. In this inactive environment, to avoid moisture contact, the dew point is preferably below -50°C, more preferably below -60°C. The aforementioned inactive gas environment refers to an environment containing inactive gases such as argon, helium, and nitrogen. To prevent impurities from contaminating the product, the higher the purity of these inactive gases, the better. As for the method of introducing inactive gases into the mixing system, there are no particular limitations as long as the mixing system is filled with an inactive gas environment; examples include methods for purifying inactive gases and methods for continuously introducing a certain amount of inactive gas.

[0062] The mixing conditions during the mechanical processing of the raw material inorganic composition (A), including rotation speed, processing time, temperature, reaction pressure, and gravitational acceleration applied to the raw material inorganic composition (A), can be appropriately determined according to the type and quantity of the raw material inorganic composition (A). Generally, the faster the rotation speed, the faster the glass formation rate, and the longer the processing time, the higher the conversion rate to glass.

[0063] Typically, when using CuKα rays as the radiation source for X-ray diffraction analysis, the disappearance or decrease of the diffraction peaks from the raw material indicates that the inorganic composition (A) of the raw material has been vitrified, and the desired sulfide-based inorganic solid electrolyte material can be obtained.

[0064] Here, in the vitrification process of the raw material inorganic composition (A), mechanical treatment is preferably performed until the lithium-ion conductivity measured by AC impedance method under the conditions of 27.0°C, applied voltage of 10mV, and measurement frequency range of 0.1Hz to 7MHz is 0.5×10⁻⁶. -4 S·cm -1 The preferred value is 1.0 × 10⁴. -4 S·cm -1 Therefore, sulfide-based inorganic solid electrolyte materials with even better lithium-ion conductivity can be obtained.

[0065] (Crystallization process)

[0066] In the method for manufacturing sulfide-based inorganic solid electrolyte materials according to this embodiment, from the viewpoint of further improving the lithium-ion conductivity of the obtained sulfide-based inorganic solid electrolyte material, it is preferable to perform a crystallization step after the vitrification step. This step involves heating the obtained sulfide-based inorganic solid electrolyte material (hereinafter, the glassy sulfide-based inorganic solid electrolyte material after the vitrification step is also referred to as inorganic composition (B)) to crystallize at least a portion of the inorganic composition (B). By heating the obtained inorganic composition (B) to crystallize at least a portion of the inorganic composition (B), a sulfide-based inorganic solid electrolyte material in a glass-ceramic state (also referred to as crystallized glass) can be obtained. This results in a sulfide-based inorganic solid electrolyte material with, for example, even better lithium-ion conductivity.

[0067] That is, from the viewpoint of excellent lithium-ion conductivity, the sulfide-based inorganic solid electrolyte material in this embodiment is preferably in the glass-ceramic state (crystallized glass state).

[0068] The temperature at which the inorganic composition (B) is heated is not particularly limited as long as it is a temperature at which sufficient crystallization can occur. For example, from the viewpoint of effectively crystallizing while suppressing the thermal decomposition of the inorganic composition (B), it is preferably in the range of 220°C or higher and 500°C or lower, more preferably in the range of 250°C or higher and 400°C or lower, more preferably in the range of 260°C or higher and 350°C or lower, and even more preferably in the range of 270°C or higher and 350°C or lower.

[0069] There are no particular limitations on the heating time of the inorganic composition (B), as long as it is sufficient to obtain the desired glass-ceramic state of the sulfide-based inorganic solid electrolyte material. For example, it can be in the range of 1 minute or more and 24 hours or less, preferably in the range of 0.5 hours or more and 8 hours or less, and more preferably in the range of 1 hour or more and 3 hours or less. There are no particular limitations on the heating method; for example, a firing furnace can be used. It should be noted that the temperature, time, and other conditions during heating can be appropriately adjusted to optimize the properties of the sulfide-based inorganic solid electrolyte material.

[0070] Furthermore, it is preferable that the heating of the inorganic composition (B) is carried out, for example, in an inert gas environment. This prevents the deterioration (e.g., oxidation) of the inorganic composition (B).

[0071] Examples of inert gases used when heating the inorganic composition (B) include argon, helium, and nitrogen. To prevent impurities from contaminating the product, higher purity of these inert gases is preferred. Furthermore, to avoid moisture contact, a dew point of -50°C or lower is preferred, and particularly -60°C or lower is especially preferred. As for the method of introducing the inert gas into the mixing system, there are no particular limitations as long as the mixing system is filled with an inert gas environment; examples include methods for purifying the inert gas and methods for continuously introducing a certain amount of inert gas.

[0072] (Heating process)

[0073] In the method for manufacturing sulfide-based inorganic solid electrolyte materials according to this embodiment, a step of heating the raw material inorganic composition (A) prepared in the preparation step can be performed between the preparation step and the vitrification step.

[0074] That is, the above-mentioned vitrification process can also be performed on the raw material inorganic composition (A) that has undergone heat treatment.

[0075] By performing a heating process prior to the aforementioned vitrification process, the vitrification process of the raw material inorganic composition (A) can be further shortened. As a result, the manufacturing time of the sulfide-based inorganic solid electrolyte material can be further shortened. The reason for this is unclear, but it is speculated to be as follows.

[0076] First, the inorganic composition in the glassy state is in a quasi-stable state. On the other hand, the inorganic composition in the crystalline state is in a stable state. Furthermore, if an inorganic composition containing two or more inorganic compounds is heated, energy exceeding the activation energy can be easily imparted, thus enabling energy release and allowing the inorganic composition to be in a low-energy crystalline state within a short time. Moreover, since the free energy of the stable state is very close to that of the quasi-stable state, it is possible to transition from the stable crystalline state to the quasi-stable glassy state with even less energy.

[0077] Based on the above reasons, it is believed that by heating the raw inorganic composition (A) before the vitrification process, the raw inorganic composition (A) can be made into a crystalline state as a stable state in advance, and can be made into a quasi-stable glass state with less energy, thus significantly shortening the vitrification process of the raw inorganic composition (A).

[0078] There is no particular limitation on the temperature at which the raw material inorganic composition (A) is heated, and it can be appropriately set according to the sulfide-based inorganic solid electrolyte material produced.

[0079] For example, the heating temperature is preferably in the range of 200°C or higher and 400°C or lower, and more preferably in the range of 220°C or higher and 300°C or lower.

[0080] There is no particular limitation on the heating time of the raw material inorganic composition (A), for example, it is in the range of 1 minute or more and 24 hours or less, preferably 0.1 hours or more and 10 hours or less. There is no particular limitation on the heating method, for example, the method of using a calcination furnace can be cited. It should be noted that, in order to make the characteristics of the sulfide-based inorganic solid electrolyte material of this embodiment most suitable, the temperature, time and other conditions during this heating can be appropriately adjusted.

[0081] In addition, whether the raw material inorganic composition (A) has crystallized can be determined, for example, by whether a new crystallization peak is generated in the spectrum obtained by X-ray diffraction using CuKα rays as the radiation source.

[0082] (The process of crushing, classifying, or granulating)

[0083] In the method for manufacturing sulfide-based inorganic solid electrolyte materials according to this embodiment, steps such as pulverizing, classifying, or granulating the obtained sulfide-based inorganic solid electrolyte material may be performed as needed. For example, by pulverizing to micronize, and then adjusting the particle size through classification or granulation operations, sulfide-based inorganic solid electrolyte materials with the desired particle size can be obtained. As for the pulverizing method, there are no particular limitations; known pulverizing methods such as mixers, air jet mills, mortars, rotary mills, and coffee mills can be used. Furthermore, as for the classification method, there are no particular limitations; known methods such as sieves can be used.

[0084] From the viewpoint of preventing contact with moisture in the air, it is preferable that these crushing or grading operations be carried out in an inactive gas environment or a vacuum environment.

[0085] To obtain the sulfide-based inorganic solid electrolyte material of this embodiment, it is important to appropriately adjust each of the above-described processes. However, the method for manufacturing the sulfide-based inorganic solid electrolyte material of this embodiment is not limited to the above-described method; by appropriately adjusting various conditions, the sulfide-based inorganic solid electrolyte material of this embodiment can be obtained.

[0086] The embodiments of the present invention have been described above. However, these are examples of the present invention, and various configurations other than those described above may also be used.

[0087] It should be noted that the present invention is not limited to the foregoing embodiments, and variations and improvements within the scope of achieving the purpose of the present invention are also included in the present invention.

[0088] Example

[0089] The present invention will now be described with reference to examples and comparative examples, but the present invention is not limited thereto.

[0090] <Evaluation Methods>

[0091] First, the evaluation methods in the following embodiments and comparative examples will be explained.

[0092] (1) Determination of lithium-ion conductivity

[0093] The lithium-ion conductivity of the sulfide-based inorganic solid electrolyte materials obtained in the examples and comparative examples was determined by electrochemical impedance spectroscopy.

[0094] The lithium-ion conductivity was measured using a potentiostat / galvanostat SP-300 manufactured by Biologic Co., Ltd. The sample size was 9.5 mm in diameter and 1.2–2.0 mm thick. The measurement conditions were: applied voltage 10 mV, measurement temperature 27.0 °C, measurement frequency range 0.1 Hz–7 MHz, and Li foil as the electrode.

[0095] Here, as a sample for measuring lithium-ion conductivity, a plate-shaped sulfide-based inorganic solid electrolyte material with a diameter of 9.5 mm and a thickness of 1.2 to 2.0 mm was obtained by pressing 150 mg of the powdered sulfide-based inorganic solid electrolyte material obtained in the examples and comparative examples at 270 MPa for 10 minutes using a pressure device.

[0096] <Example 1>

[0097] (1) Preparation of sulfide-based inorganic solid electrolyte material 1 for crystallization nucleation agent

[0098] The following steps are used to prepare sulfide-based inorganic solid electrolyte material 1 for use as a crystal nucleating agent.

[0099] As raw materials, Li2S (manufactured by Furukawa Metal Industries, 99.9% purity), P2S5 (manufactured by Kanto Chemical Co., Ltd.), and Li3N (manufactured by Furukawa Metal Industries, Ltd.) were used.

[0100] Next, in an argon glove box, Li2S powder, P2S5 powder, and Li3N powder were precisely weighed (Li2S:P2S5:Li3N = 27:9:2 (molar ratio)), and all powders were mixed in an agate mortar for 10 minutes.

[0101] Next, 1g of the mixed powder was weighed and placed together with 18 φ10mm zirconia balls into a zirconia container (45mL internal volume). The mixture was then pulverized and mixed using a planetary ball mill (800rpm rotation, 400rpm revolution) for 30 minutes to obtain a glassy sulfide-based inorganic solid electrolyte material (Li). 10 P3S 12 ).

[0102] Next, the glass-state sulfide-based inorganic solid electrolyte material was annealed in argon at 290°C for 2 hours to obtain a glass-ceramic-state sulfide-based inorganic solid electrolyte material (Li). 10 P3S 12 Next, the obtained glass-ceramic state sulfide-based inorganic solid electrolyte material was pulverized and mixed for 30 hours using a planetary ball mill (rotation 800 rpm, revolution 400 rpm) and then revitrified to obtain sulfide-based inorganic solid electrolyte material 1 for crystal nucleation.

[0103] (2) Preparation of target sulfide-based inorganic solid electrolyte materials

[0104] The target sulfide-based inorganic solid electrolyte material was prepared using the following steps.

[0105] As raw materials, Li2S (manufactured by Furukawa Metal Industries, 99.9% purity), P2S5 (manufactured by Kanto Chemical Co., Ltd.), and Li3N (manufactured by Furukawa Metal Industries, Ltd.) were used.

[0106] Next, in an argon glove box, accurately weigh Li2S powder, P2S5 powder, and Li3N powder (Li2S:P2S5:Li3N = 27:9:2 (molar ratio)). Accurately weigh these raw material powders to ensure that the sulfide-based inorganic solid electrolyte material 1 used as the crystal nucleating agent reaches the content shown in Table 1. Mix all the powders with an agate mortar for 10 minutes.

[0107] Next, 1 g of the mixed powder (raw material inorganic composition (A)) was weighed and placed together with 18 φ10 mm zirconia balls into a zirconia container (internal volume 45 mL). The mixture was then pulverized and mixed using a planetary ball mill (800 rpm rotation, 400 rpm revolution) for 3 hours (mechanical-chemical treatment) to obtain a glassy sulfide-based inorganic solid electrolyte material (Li). 10 P3S 12 ).

[0108] Next, the glass-state sulfide-based inorganic solid electrolyte material was annealed in argon at 290°C for 2 hours to obtain a glass-ceramic-state sulfide-based inorganic solid electrolyte material (Li). 10 P3S 12 ).

[0109] The lithium-ion conductivity of the obtained sulfide-based inorganic solid electrolyte materials in both glass and glass-ceramic states was measured. The results are shown in Table 1.

[0110] <Examples 2-4 and Comparative Example 1>

[0111] Except for changing the content of the sulfide-based inorganic solid electrolyte material 1 used as the nucleating agent as shown in Table 1, the same procedure was followed as in Example 1 to prepare sulfide-based inorganic solid electrolyte materials in a glassy state and sulfide-based inorganic solid electrolyte materials in a glass-ceramic state (Li). 10 P3S 12 The lithium-ion conductivity of the obtained glass-state sulfide-based inorganic solid electrolyte material and the glass-ceramic-state sulfide-based inorganic solid electrolyte material was measured. The results are shown in Table 1.

[0112] <Examples 5-9>

[0113] Except for changing the time of mechanochemical treatment by planetary ball mill as shown in Table 1, the same procedure was followed as in Example 2 to prepare sulfide-based inorganic solid electrolyte materials in glassy state and sulfide-based inorganic solid electrolyte materials in glass-ceramic state (Li). 10 P3S 12 The lithium-ion conductivity of the obtained glass-state sulfide-based inorganic solid electrolyte materials and glass-ceramic-state sulfide-based inorganic solid electrolyte materials was measured. The results are shown in Table 1.

[0114] <Examples 10-11 and Comparative Examples 2-3>

[0115] (1) Preparation of sulfide-based inorganic solid electrolyte material 2 for crystal nucleating agent

[0116] Except for adjusting the proportions of each raw material to achieve the composition of Li3PS4, the same process as for sulfide-based inorganic solid electrolyte material 1 used as a nucleating agent was carried out to prepare sulfide-based inorganic solid electrolyte material 2 used as a nucleating agent.

[0117] (2) Preparation of target sulfide-based inorganic solid electrolyte materials

[0118] Except for adjusting the proportions of the raw materials to achieve the Li3PS4 composition, changing the mechanochemical treatment time via planetary ball mill as shown in Table 1, and changing the type and content of the sulfide-based inorganic solid electrolyte material used as the nucleating agent as shown in Table 1, the process was carried out in the same manner as in Example 1. Glass-state and glass-ceramic-state sulfide-based inorganic solid electrolyte materials (Li3PS4) were prepared respectively. The lithium-ion conductivity of the obtained glass-state and glass-ceramic-state sulfide-based inorganic solid electrolyte materials was measured. The results are shown in Table 1.

[0119] Table 1

[0120]

[0121] It is understood that when comparing the mechanochemical processing time and the type of sulfide-based inorganic solid electrolyte material, the method for manufacturing the sulfide-based inorganic solid electrolyte material in the embodiments can obtain sulfide-based inorganic solid electrolyte materials with high ionic conductivity in a short time.

[0122] Therefore, it can be understood that the method for manufacturing sulfide-based inorganic solid electrolyte materials according to this embodiment can vitrify the inorganic composition in a shorter time, thereby shortening the manufacturing time.

[0123] This application is based on and claims priority to Japanese Patent Application No. 2019-066565, filed on March 29, 2019, the entire contents of which are incorporated herein by reference.

Claims

1. A raw material inorganic composition, which is used in the manufacture of sulfide-based inorganic solid electrolyte materials containing Li, P, and S as constituent elements, wherein, The raw material inorganic composition contains at least lithium sulfide, phosphorus sulfide, and a nucleating agent. The nucleating agent comprises a sulfide-based inorganic solid electrolyte material containing Li, P, and S as constituent elements. The raw material inorganic composition is the raw material inorganic composition prior to the vitrification process.

2. The raw material inorganic composition as described in claim 1, wherein, The molar ratio of Li to P content in the sulfide-based inorganic solid electrolyte material, which serves as the nucleating agent for crystallization, is 1.0 or more and 10.0 or less, and the molar ratio of S to P content is 1.0 or more and 10.0 or less.

3. The raw material inorganic composition as described in claim 1 or 2, wherein, The content of the nucleating agent is 5% by mass or more and 60% by mass or less.

Citation Information

Patent Citations

  • Sulfide solid electrolytic material, battery, and method for manufacturing sulfide solid electrolytic material

    JP2016027545A

  • Liquid crystal display device

    JP2019066565A

  • Sulfide electrolyte material and preparation method thereof

    CN103500853A

  • Method for guiding crystal growth to prepare high-density and high-conductivity electrolyte sheets

    CN109244549A

  • Lithium ion conducting sulfide based crystallized glass and method for production thereof

    CN1918668A